Detection of Anomaly Actions on Social Networks using Machine Learning - Jain, Mayur; Prashanth, A; B K, Prabhudev; Sagar Reddy N J,; , Mangala C N (International Journal of Computer Sciences and Engineering, 2025)
Social media is no doubt the richest source of human generated data. The user’s options, feedbacks and critiques provided by social network users reflect attitudes and sentiments of certain topics, products, or services. Every day, large quantity of messages is created, stored, commented, and shared by people on social media websites, such as Twitter, Instagram, Quora and Facebook. This in general acts as valuable data for researchers and practitioners in different application domains, such as data analytics, marketing, to inform decision-making. Extracting valuable social signals from the huge crowd’s messages is challenging, due to the dynamic crowd behaviors. These are the anomalies caused by a user because of his/her variable behavior towards different sources. Due to such risk parameters, it is always a great practice to have a mechanism to monitor each online social network user. This paper provides a way in which anomaly analysis can be implemented in social media such as Facebook. This work hence acts as a risk analyzer for the administrator of the Face book services so that they can formulate strategies to overcome the same.